PERAN PROFITABILITAS SEBAGAI MODERATING VARIABEL DARI PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN - Junardi Junardi; Vivi Vivi; Sugianto Sugianto; Wui San Taslim (Jurnal Pendidikan Ekonomi (JURKAMI), 2022)
The prosperity of shareholders depends on the firm value. The fluctuations in firm value are inseparable from management's performance in managing company. This research aims to examine effect of Good Corporate Governance is measured by institusional ownership and independent commissioners, and profitability on firm value and the effect of Good Corporate Governance on firm value with profitability as the moderating variable. The sampling technique used was purposive sampling judgment method. The sample used in this study amounted 43 companies from a total population of 62 Food and Beverage Subsector Companies listed on the IDX for the 2017-2020 period. This research performed with assosiative quantitative method. The data analysis technique in this study is the moderation regression analysis. The results shows that Good Corporate Governance and profitability have no significant effect on firm value. Profitability is able to moderate the relationship between Good Corporate Governance on firm value.